2006
DOI: 10.1136/jnnp.2006.103549
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor profile of cerebral small vessel disease and its subtypes

Abstract: SVD has a different risk factor profile from the typical atherosclerotic profile found in LVD, with hypertension being important. There are differences in the risk factor profile between the SVD subtypes; the association of ILI with hypercholesterolaemia, diabetes and myocardial infarction may be consistent with a more atherosclerotic aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
165
6
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(190 citation statements)
references
References 26 publications
15
165
6
4
Order By: Relevance
“…However, the association between LA and cerebrovascular risk factors is still being debated; Murray et al 56 found a significant Pearson correlation between LA and diabetes, hypertension, low-attenuation lipoprotein, and cholesterol, but these associations were not confirmed by other authors. 57 An interesting result observed in our study was the association between the presence of the fatty plaque type and LA (P ϭ 0.0276). It is well known that the composition of the atherosclerotic plaque may play a significant role in the origin of cerebrovascular events.…”
Section: Discussionsupporting
confidence: 52%
“…However, the association between LA and cerebrovascular risk factors is still being debated; Murray et al 56 found a significant Pearson correlation between LA and diabetes, hypertension, low-attenuation lipoprotein, and cholesterol, but these associations were not confirmed by other authors. 57 An interesting result observed in our study was the association between the presence of the fatty plaque type and LA (P ϭ 0.0276). It is well known that the composition of the atherosclerotic plaque may play a significant role in the origin of cerebrovascular events.…”
Section: Discussionsupporting
confidence: 52%
“…Hypertension, found in 65% of all subjects in the Three-City Study (11), is the main risk factor for cerebral small vessel disease (20). Cerebral small vessel disease induces silent ischemia in both the perforating arteries of the thalami and the leptomeningeal or cortical vessels of the insula.…”
Section: Discussionmentioning
confidence: 99%
“…SVD has different risk factors from large vessel diseases. Hypertension is more common in SVD than large vessel diseases, whereas hypercholesterolemia, smoking, myocardial infarction and peripheral vascular disease are more common in large vessel diseases (64). Hypertension may induce fibrohyalinosis with thickening of the wall and narrowing of the vascular lumen on the small penetrating arteries and arterioles of the white matter.…”
Section: Etiologic Factorsmentioning
confidence: 99%